Job Involvement, Work Facilities, and Work Environment Influence Turnover Intention of Outsourced Employees (PT Angkasa Pura Solusi Integra - Soekarno Hatta Intenational Airport) - Eki Rizky Juniar; Muhammad Imam Muttaqijn; Dudung Hadiwijaya (Quantitative Economics and Management Studies, 2024)
This study provides insights into determining the influence of Job Involvement, workplace facilities, and work environment on the Turnover Intention of outsourcing employees at PT. Angkasa Pura Solusi Integra (Soekarno Hatta International Airport). The research employed a quantitative approach with a total of 327 respondents from a population of 1801, which included outsourcing employees such as Avsec, Cleaning Service, Security PMAD, Trolley Collectors, Basket Collectors, and others. Simple random sampling was utilized as the sampling method. The primary data collected in this study involved questionnaires and direct observations. Data analysis was conducted using multiple linear regression techniques. Based on the research findings, both partially and simultaneously, it can be concluded that there is a significant negative influence of Job Involvement, Workplace Facilities, and Work Environment on the Turnover Intention of outsourcing employees.